Organization of Afferents along the Anterior–posterior and Medial–lateral Axes of the Rat Orbitofrontal Cortex - Barreiros, Ines V. (Neuroscience, 2021)
The orbitofrontal cortex (OFC) has been anatomically divided into a number of subregions along its medial–lateral axis, which behavioral research suggests have distinct functions. Recently, evidence has emerged suggesting functional diversity is also present along the anterior–posterior axis of the rodent OFC. However, the patterns of anatomical connections that underlie these differences have not been well characterized. Here, we use the retrograde tracer cholera toxin subunit B (CTB) to simultaneously label the projections into the anterior lateral (ALO), posterior lateral (PLO), and posterior ventral (PVO) portions of the rat OFC. Our methodological approach allowed us to simultaneously compare the density and input patterns into these OFC subdivisions. We observed distinct and topographically organized projection patterns into ALO, PLO, and PVO from the mediodorsal and the submedius nuclei of the thalamus. We also observed different levels of connectivity strength into these OFC subdivisions from the amygdala, motor cortex, sensory cortices and medial prefrontal cortical structures, including medial OFC, infralimbic and prelimbic cortices. Interestingly, while labelling in some of these input regions revealed only a gradient in connectivity strength, other regions seem to project almost exclusively to specific OFC subdivisions. Moreover, differences in input patterns between ALO and PLO were as pronounced as those between PLO and PVO. Together, our results support the existence of distinct anatomical circuits within lateral OFC along its anterior–posterior axis.